Hydrocracking catalyst as well as preparation method and application thereof
By using mesoporous-rich Y-type molecular sieve as a support and loading metal active components, a hydrocracking catalyst with a special structure was prepared, which solved the problem of unstable performance of existing catalysts when dealing with heavy distillates, and achieved the Efficient catalytic activity and stability, suitable for long-term operation and high-quality tail oil production.
Patent Information
- Application Number
- CN202310954150.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hydrocracking catalysts have unstable performance when treating heavy distillates, and have a long service life, making it difficult to meet the improvement of processing capacity.
A hydrocracking catalyst with a special structure was prepared by using a mesoporous-rich Y-shaped molecular sieve as a support and supporting the metal active components. The mesoporous structure of the catalyst and the combination of metal active components improves catalytic activity and stability.
It achieves higher catalytic activity and stability in hydrocracking reaction, extends the service cycle of the device, and has high alkane content and low BMCI value tail oil performance.
Smart Images

Figure CN119425769A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of hydrocracking, and in particular, to a hydrocracking catalyst and a preparation method and application thereof. Background Art
[0002] As crude oil becomes heavier and inferior, the conversion of heavy distillate oil has become a difficult problem in refining catalysts and technologies. Hydrocracking is one of the key technologies for lightening oil products. In the processing of heavy oil products, polycyclic hydrocarbons, especially cycloalkanes and aromatic hydrocarbons with three or more rings, accumulate in the circulating oil, resulting in reduced catalyst activity and shortened operating cycles.
[0003] Hydrocracking technology is one of the classic means of hydrogenation conversion of heavy distillate oil, with the characteristics of high product quality, long service life, and flexible operation. It is used to process conventional oil products, such as VGO and LCO, and has advantages that other technologies do not have. However, when used to process heavy distillates, especially heavy distillates with a dry point greater than 600°C, problems such as unstable catalyst performance and long service life often occur.
[0004] Improving the processing capacity of heavy distillate oil in hydrocracking technology mainly depends on hydrocracking catalysts. Hydrocracking catalyst is a bifunctional catalyst that has both cracking activity and hydrogenation activity, that is, it contains both acidic components and hydrogenation active components. Its acidity is mainly provided by heat-resistant inorganic oxides and / or various zeolites constituting the carrier; the hydrogenation active components are generally selected from metals, metal oxides and / or metal sulfides of Groups VIB and VIIIB in the periodic table. In order to meet different requirements for hydrocracking products, it is necessary to adaptively adjust the acidic components and hydrogenation active components in the catalyst.
[0005] For hydrocracking catalysts, the improvement of catalyst performance requires, on the one hand, further improvement of hydrogenation performance; on the other hand, it requires suitable acidic components so that the cracking or isomerization performance can match the target product. Selecting molecular sieves or mesoporous materials, or even solid superacids, can adjust the properties of the acidic components within a larger range, thereby optimizing the acidic function of the catalyst. However, the space for adjusting the performance of the hydrogenation component is limited. Although precious metals can be used as hydrogenation components, they generally cannot process sulfur-containing raw materials. Therefore, the hydrogenation component of industrial hydrocracking catalysts generally selects non-precious metals as hydrogenation components. The hydrogenation activity of non-precious metals is lower than that of precious metals, and often cannot meet the requirements. How to improve the hydrogenation performance of the catalyst has become a problem that some hydrocracking catalysts need to solve.
[0006] Using non-precious metal components as hydrogenation components, the microscopic properties of hydrogenation components have a great influence on the performance of catalysts, and there are many patents on catalyst preparation at home and abroad. By selecting different metal components, the hydrogenation performance of the catalyst can be improved. For example, if the metal component is Ni-W component, its hydrogenation activity can be higher than that of Ni-Mo and Co-Mo catalysts (Contact Catalysis, Principle Preparation and Application of Industrial Catalysts, JF Lebarri et al., translated by Li Xuanwen and Huang Zhiyuan, Petroleum Industry Press, Beijing, 1984, p207).
[0007] Acidic components can be divided into two categories according to the degree of crystallization: molecular sieves and amorphous silica-alumina. Molecular sieves are used for catalysts that require more acid centers and high reactivity. Compared with molecular sieves, amorphous silica-alumina has a simple preparation method, low cost, larger pore size, larger silica-alumina ratio adjustment range and lower acid density. It is particularly suitable for processing macromolecular raw materials such as heavy oil and residual oil; it is often used in catalysts that require lower acid density, such as hydrocracking catalysts and hydroisomerization catalysts with high middle distillate selectivity. Amorphous silica-alumina is an acid carrier for many industrial amorphous catalysts and an important component of many molecular sieve catalysts, but the common disadvantage of amorphous silica-alumina materials is low cracking activity.
[0008] For the production of high-quality tail oil, an important key point is how to increase the conversion of cycloalkanes and reduce the conversion of paraffins, that is, to improve the cracking selectivity of cycloalkanes. Generally speaking, under the same carbon number conditions, since cycloalkanes have a rigid ring structure, their molecular size is larger than that of paraffins, and the adsorption performance of cycloalkanes is also higher than that of paraffins; the cracking rate of paraffins under the same conditions is higher than that of cycloalkanes, especially higher than the ring opening rate of cycloalkanes, that is, paraffins are more soluble and cracked. To improve the cracking selectivity of cycloalkanes, it is necessary to take advantage of the stronger adsorption performance of cycloalkanes and improve the cracking selectivity of cycloalkanes by reducing the chance of paraffins participating in the reaction. Therefore, a surface acidity with a larger pore size and stronger accessibility to cycloalkanes is crucial.
[0009] Chinese patent CN 114835135 A proposes a titanium-containing gas-phase ultrastable mesoporous Y zeolite and its preparation method and application. The secondary pore area of the obtained USY molecular sieve can reach up to 266m 2 / g, but the molecular sieve contains more than 10% TiO2, which may affect the acidity and pore structure of the molecular sieve.
[0010] Chinese patent CN 111689504 A proposes a method for preparing a meso-micro hierarchical pore structure Y-type zeolite molecular sieve, which includes: mixing NaY zeolite molecular sieve, ammonium salt and water, stirring, filtering and washing to obtain ammonium type Y-type zeolite molecular sieve; mixing ammonium type Y-type zeolite molecular sieve, boron-containing compound and water, and then filtering, washing, and finally high-temperature hydrothermal treatment to obtain meso-micro hierarchical pore structure Y-type zeolite molecular sieve. The secondary pore area of the obtained USY molecular sieve can reach up to 105m 2 / g. Since boron-containing compounds are used as pore-forming aids and the patent does not mention the acidity and boron content of the molecular sieve, it is expected that the acid density of the molecular sieve is also relatively low.
[0011] Chinese patent CN 114713271 A proposes a modified Y molecular sieve and its preparation method, using small-grain Y molecular sieve as raw material and alkali treatment to obtain a USY molecular sieve with a secondary pore area of up to 410m 2 / g, but for molecular sieves with larger secondary pore area, the silicon-aluminum ratio is also higher, and the acid density is difficult to guarantee.
[0012] Chinese patent CN 112408416 A proposes a Y-type molecular sieve rich in secondary pores and its preparation method, the method used is: mix and stir the raw material Y-type molecular sieve with an inorganic acid solution to obtain a mixed solution; add an inorganic alkali solution to the mixed solution to obtain a mixture; wash, filter and dry the mixture to obtain a Y-type molecular sieve rich in secondary pores. That is, first use inorganic acid treatment to increase the silicon-aluminum ratio of the molecular sieve, and then use inorganic alkali treatment to construct the secondary pore content, so as to prepare a Y-type molecular sieve rich in secondary pores. The secondary pore area of the obtained USY molecular sieve can reach up to 268m 2 / g. Due to the acid treatment first, the silicon-aluminum ratio of the molecular sieve is relatively high and the acid density is relatively low.
[0013] Chinese patent ZL 201811105225.8 proposes a multi-level pore FAU structure molecular sieve and its preparation method, the preparation method comprising: steam treatment and alkali treatment of the FAU structure molecular sieve precursor, and calcination of the treated product. The secondary pore area of the obtained USY molecular sieve can reach up to 260m 2 / g. Since no data on the framework silicon-to-aluminum ratio or unit cell constant are provided, the acidity of the molecular sieve cannot be determined. However, due to the need for steam treatment, it is expected that the molecular sieve has a relatively high silicon-to-aluminum ratio and a relatively low acid density.
[0014] Chinese patent ZL201410045450.2 proposes a method for preparing small-grain Y-type molecular sieves. This patent uses NaY-type molecular sieve raw materials with high silicon-aluminum ratio, high crystallinity and good stability. After ammonium exchange, first hydrothermal treatment, alkaline solution treatment, second hydrothermal treatment and mixed solution treatment with acid and ammonium salt, the obtained small-grain Y-type molecular sieve is obtained. The secondary pore area of the obtained USY molecular sieve can reach up to 293m 2 / g, and the silicon-aluminum ratio of the molecular sieve also reaches 113, and the acid density is close to 0.
[0015] Chinese patent ZL201410045479.0 proposes a method for preparing a hydrocracking catalyst carrier. This method uses a NaY molecular sieve raw material with a high silicon-aluminum ratio, high crystallinity and good stability, and sequentially undergoes alkali washing, ammonium exchange, dealumination and silicon supplementation, hydrothermal treatment and treatment with a mixed solution of acid and ammonium salt to obtain a small-grain Y molecular sieve. The secondary pore area of the obtained USY molecular sieve can reach up to 249m 2 / g, and the silicon-aluminum ratio of the molecular sieve reaches 84, and the acid density is extremely low.
[0016] Chinese patent CN104760973A proposes a Y-type molecular sieve with ultra-high mesoporous content and its preparation method, which includes: pre-treating the Y-type zeolite at 300-600℃ for 1-5h; cooling to 200-600℃; in a water-free dry environment, introducing dry gas saturated with dealuminized silicon-replenishing agent into the pre-treated Y-type zeolite, reacting for 0.5-7h to obtain a crude product; or in a water-free dry environment, while uniformly heating the temperature to 250℃-700℃, introducing dry gas saturated with dealuminized silicon-replenishing agent into the pre-treated Y-type zeolite, reacting for 0.5-7h to obtain a crude product; the introduction rate of dry gas saturated with dealuminized silicon-replenishing agent is 50mL / min; acid treatment of the crude product; alkali treatment of the acid-treated crude product to obtain a Y-type molecular sieve. The secondary pore area of the obtained USY molecular sieve can reach up to 310.6m 2 / g, and the silicon-aluminum ratio of the molecular sieve also reaches 40.9, and the acid density is low. Summary of the invention
[0017] The purpose of the present disclosure is to provide a hydrocracking catalyst and a preparation method and application thereof. The catalyst is used for the hydrocracking reaction of hydrocarbon feedstock oil and can obtain higher catalytic activity and stability.
[0018] In order to achieve the above object, the present disclosure provides a method for preparing a hydrocracking catalyst in a first aspect, the method comprising the following steps:
[0019] S1, forming a Y-type molecular sieve rich in mesopores to obtain a carrier;
[0020] S2, loading metal active components on the carrier;
[0021] The unit cell parameter of the mesoporous Y-type molecular sieve is 24.35-24.55 angstroms, the relative crystallinity is more than 55%, and the specific surface area of the mesopores is 250-400 m 2 / g;
[0022] The mesopore-rich Y-type molecular sieve has mesopores with pore diameters in the ranges of 3-4.5 nm, 5.5-11.0 nm and 12.5-36 nm.
[0023] Optionally, the unit cell parameter of the Y-type molecular sieve is 24.40-24.52 angstroms, and the specific surface area of the mesopores is 270-350 m 2 / g, and the relative crystallinity is 56-70%.
[0024] Optionally, the total volume of mesopores with pore sizes in the range of 3-4.5 nm is 0.038-0.045 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 5.5 to 11.0 nm is 0.015 to 0.020 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 12.5 to 36 nm is 0.350 to 0.410 cm 3 / g;
[0025] The total volume of the micropores is 0.180-0.300 cm 3 / g, and the total volume of the mesopores is 0.403-0.475cm 3 / g, with a total pore volume of 0.583-0.775 cm 3 / g, total specific surface area is 700-800m 2 / g;
[0026] The total volume of mesopores accounts for 53-70% of the total pore volume.
[0027] The method for preparing the mesoporous Y-type molecular sieve comprises the following steps:
[0028] a. subjecting the NaY molecular sieve to an acid exchange treatment to obtain a first product, wherein the pH value of the acid exchange treatment is 2.5-3.5;
[0029] b. subjecting the first product to a first hydrothermal roasting treatment to obtain a second product;
[0030] c. subjecting the second product to a first ammonium exchange treatment to obtain a third product;
[0031] Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %;
[0032] d. subjecting the third product to a second hydrothermal roasting treatment to obtain a fourth product;
[0033] e. contacting the fourth product, alkali and water, and performing alkali treatment to obtain a mixed slurry containing a fifth product;
[0034] f. contacting the aluminum-containing compound with the mixed slurry, and sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment;
[0035] g. subjecting the sixth product obtained in step f to a second ammonium exchange treatment to obtain a seventh product;
[0036] h. subjecting the seventh product to urea modification treatment;
[0037] The temperature of the first aluminum addition treatment is higher than the temperature of the second aluminum addition treatment.
[0038] Optionally, step a comprises: contacting the NaY molecular sieve with an acidic solution, performing the acid exchange treatment, and then performing solid-liquid separation, washing and drying treatment on the obtained mixture to obtain the first product;
[0039] The acidic solution includes one or more of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, citric acid solution, oxalic acid solution and tartaric acid solution;
[0040] The conditions of the acid exchange treatment include: temperature of 30-80°C, preferably 35-70°C; time of 0.5-2h, preferably 0.5-1h;
[0041] The silicon-aluminum ratio of the NaY molecular sieve is 4.8-5.0, and the crystallinity is above 80%. The silicon-aluminum ratio is the molar ratio of SiO2 to Al2O3 in the NaY molecular sieve;
[0042] The pH value of the acid exchange treatment is 2.8-3.1.
[0043] Optionally, in step b, the conditions of the first hydrothermal calcination treatment include: a treatment atmosphere of 100% water vapor atmosphere, a temperature of 500-600° C., and a time of 1-3 h.
[0044] Optionally, the first ammonium exchange treatment comprises: contacting the second product with an aqueous solution containing an ammonium salt to perform the first ammonium exchange treatment;
[0045] The weight ratio of the ammonium salt to the second product on a dry basis is 1:(0.1-1);
[0046] The conditions of the first ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C;
[0047] The second ammonium exchange treatment comprises: contacting the sixth product with an aqueous solution containing an ammonium salt to perform the second ammonium exchange treatment;
[0048] The weight ratio of the ammonium salt to the sixth product on a dry basis is 1:(0.1-1);
[0049] The conditions of the second ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C;
[0050] The ammonium salt includes one or more of ammonium chloride, ammonium sulfate and ammonium nitrate.
[0051] Optionally, in step d, the conditions of the second hydrothermal roasting treatment include: the treatment atmosphere is 100% water vapor atmosphere, the temperature is 550-750° C., preferably 600-700° C.; the time is 0.5-4 h, preferably 1-2.5 h.
[0052] Optionally, in step e, the base comprises an inorganic base, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide and ammonia water;
[0053] The weight ratio of the fourth product to the base on a dry basis is 1:(0.02-0.5), preferably 1:(0.05-0.4);
[0054] The conditions of the alkali treatment include: time of 0.5-6h and temperature of 25-100°C.
[0055] Optionally, in step f, the aluminum-containing compound includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum acetate and sodium aluminate;
[0056] The weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on an Al2O3 basis is 1:(0.03-0.3), preferably 1:(0.035-0.28);
[0057] The conditions of the first stage of aluminum addition treatment include: time of 0.5-3h, temperature of 70-100°C;
[0058] The conditions of the second stage of aluminum addition treatment include: time of 0.5-2h, temperature of 30-60°C.
[0059] Optionally, in step h, the urea modification treatment includes: contacting the seventh product and urea with water, and drying the obtained solid product;
[0060] The weight ratio of the seventh product to the urea on a dry basis is 1:(0.02-0.3);
[0061] The contact conditions include: time of 0.1-12h, temperature of 25-100°C;
[0062] The drying conditions include: time of 0.5-10 hours and temperature of 50-105°C.
[0063] Optionally, the carrier has a pore size of 3-20 nm and a pore size concentration of 0.3 or more.
[0064] Optionally, step S1 comprises: mixing the mesoporous Y-type molecular sieve, a heat-resistant inorganic component source, a molding component and an optional acidic component source, and then extruding and molding and calcining to obtain the carrier;
[0065] The heat-resistant inorganic component source includes a heat-resistant inorganic oxide and / or a heat-resistant inorganic oxide precursor;
[0066] Preferably, the heat-resistant inorganic oxide includes one or more of SiO2, Al2O3, MgO, ZrO2, TiO2 and CaO;
[0067] The heat-resistant inorganic oxide precursor includes one or more of silica sol, water glass, pseudo-boehmite, Mg(OH)2, MgCO3, hydrated titanium oxide, titanyl sulfate, Ca(OH)2 and CaCO3;
[0068] The molding components include an extrusion aid and / or an adhesive;
[0069] Preferably, the extrusion aid includes one or more of a monocarboxylic acid having 1 to 10 carbon atoms, a dicarboxylic acid having 2 to 10 carbon atoms, a saturated diol having 2 to 5 carbon atoms, a saturated triol having 3 to 5 carbon atoms, urea, an alcoholamine having 1 to 5 carbon atoms, and a surfactant;
[0070] The adhesive comprises one or more of nitric acid, citric acid, cellulose derivatives, starch and starch derivatives;
[0071] The calcination conditions include: a calcination time of 1-10 hours and a temperature of 350-800°C.
[0072] Optionally, step S2 includes:
[0073] A. contacting the carrier with a mixed solution containing an active metal source to obtain a pre-product;
[0074] B. drying and calcining the pre-product;
[0075] The active metal source includes a soluble compound of a Group VIII metal and / or a soluble compound of a Group VIB metal;
[0076] In step A, the contact reaction conditions include: time of 0.5-12h, temperature of 5-150°C;
[0077] In step B, the drying conditions include: time of 0.5-24h, temperature of 80-350°C;
[0078] The conditions of the calcination treatment include: time of 0.2-12h, temperature of 360-700°C;
[0079] Optionally, relative to the total weight of the carrier and the active metal source, the amount of the carrier is 40-99.9 wt %, the amount of the active metal source is 0.1-60 wt %, and the weight of the active metal source is calculated as oxide.
[0080] A second aspect of the present disclosure provides a hydrocracking catalyst prepared by the method described in the first aspect of the present disclosure.
[0081] Optionally, the hydrocracking catalyst comprises a carrier and a metal active component supported on the carrier, and the carrier comprises a mesoporous Y-type molecular sieve;
[0082] Optionally, the hydrocracking catalyst has a pore size of 3-20 nm and a pore size concentration of 0.3 or more.
[0083] Optionally, the metal active component comprises a metal oxide, preferably an oxide of a Group VIII metal and / or an oxide of a Group VIB metal;
[0084] The carrier also includes a heat-resistant inorganic component and an optional acidic component;
[0085] The acidic component includes one or more of ZRP molecular sieve, mordenite, ZSM-5 molecular sieve, MCM-41 molecular sieve, Ω molecular sieve, ZSM-12 molecular sieve, MCM-22 molecular sieve and composite metal oxide;
[0086] Preferably, the composite metal oxide includes one or more of aluminum silicon composite oxide, aluminum titanium composite oxide, aluminum magnesium composite oxide, silicon magnesium composite oxide, silicon zirconium composite oxide, silicon thorium composite oxide, silicon beryllium composite oxide, silicon titanium composite oxide and titanium zirconium composite oxide.
[0087] Optionally, relative to the total weight of the hydrocracking catalyst, the content of the carrier is 40-99.9 wt %, and the content of the metal active component is 0.1-60 wt % calculated as oxide.
[0088] The third aspect of the present disclosure provides a method for a hydrocracking reaction, comprising: contacting a hydrocarbon feedstock oil, a catalyst and hydrogen, and performing the hydrocracking reaction, wherein the catalyst comprises the hydrocracking catalyst described in the second aspect of the present disclosure.
[0089] Optionally, the conditions of the hydrocracking reaction include: temperature of 200-650°C, pressure of 3-24 MPa, liquid hourly space velocity of 0.1-30 h -1 , the volume ratio of hydrogen to oil is 600-1500.
[0090] Optionally, the boiling point of the hydrocarbon feedstock oil is 370-690°C;
[0091] Preferably, the hydrocarbon feedstock oil includes one or more of vacuum gas oil, demetallized oil, atmospheric residue oil, deasphalted vacuum residue oil, vacuum residue oil, coking distillate oil, shale oil, asphalt sand oil and coal liquefaction oil.
[0092] Through the above technical scheme, the present invention uses a mesoporous Y-type molecular sieve with a specific structure as a carrier and loads metal active components to prepare a hydrocracking catalyst with a special structure, which is used for the hydrocracking reaction of hydrocarbon feedstock oil. The produced tail oil has a lower BMCI value, a higher viscosity index and a higher paraffin content, and can obtain higher catalytic activity and stability, which can meet the long-term operation of the device and can also produce aviation fuel.
[0093] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0094] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0095] Figure 1 This is the pore size distribution diagram of the Y-type molecular sieve A prepared in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0096] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0097] The first aspect of the present disclosure provides a method for preparing a hydrocracking catalyst, the method comprising the following steps:
[0098] S1, forming a Y-type molecular sieve rich in mesopores to obtain a carrier;
[0099] S2, loading metal active components on the carrier;
[0100] The unit cell parameter of the mesoporous Y-type molecular sieve is 24.35-24.55 angstroms, the relative crystallinity is more than 55%, and the specific surface area of the mesopores is 250-400 m 2 / g;
[0101] The mesopore-rich Y-type molecular sieve has mesopores with pore diameters in the ranges of 3-4.5 nm, 5.5-11.0 nm and 12.5-36 nm.
[0102] According to one embodiment of the present disclosure, the unit cell parameters of the Y-type molecular sieve are 24.40-24.52 angstroms, and the specific surface area of the mesopores is 270-350 m 2 / g, and the relative crystallinity is 56-70%.
[0103] In the present disclosure, "relative crystallinity" refers to the ratio of the crystallinity of the Y-type molecular sieve of the present disclosure to the crystallinity of a standard sample, which can be measured using the RIPP146-90 standard method. The standard sample is the NaY molecular sieve produced by Qilu Catalysis Company, and the crystallinity is positioned at 100%.
[0104] In the present disclosure, "unit cell parameter" refers to the maximum dimension of a single unit cell of the Y-type molecular sieve.
[0105] In the present disclosure, "micropore" refers to a pore with a pore size less than 2 nm, and "mesopore" refers to a pore with a pore size in the range of 2-100 nm.
[0106] According to one embodiment of the present disclosure, the total volume of mesopores in the mesoporous Y-type molecular sieve with a pore size in the range of 3-4.5 nm is 0.038-0.045 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 5.5 to 11.0 nm is 0.015 to 0.020 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 12.5 to 36 nm is 0.350 to 0.410 cm 3 / g.
[0107] According to one embodiment of the present disclosure, the total volume of the micropores is 0.180-0.300 cm 3 / g, and the total volume of the mesopores is 0.403-0.475cm 3 / g, with a total pore volume of 0.583-0.775 cm 3 / g, total specific surface area is 700-800m 2 / g, and the total volume of mesopores accounts for 53-70% of the total pore volume.
[0108] According to one embodiment of the present disclosure, the method for preparing the mesoporous Y-type molecular sieve comprises the following steps:
[0109] a. subjecting the NaY molecular sieve to an acid exchange treatment to obtain a first product, wherein the pH value of the acid exchange treatment is 2.5-3.5;
[0110] b. subjecting the first product to a first hydrothermal roasting treatment to obtain a second product;
[0111] c. subjecting the second product to a first ammonium exchange treatment to obtain a third product;
[0112] Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %;
[0113] d. subjecting the third product to a second hydrothermal roasting treatment to obtain a fourth product;
[0114] e. contacting the fourth product, alkali and water, and performing alkali treatment to obtain a mixed slurry containing a fifth product;
[0115] f. contacting the aluminum-containing compound with the mixed slurry, and sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment;
[0116] g. subjecting the sixth product obtained in step f to a second ammonium exchange treatment to obtain a seventh product;
[0117] h. subjecting the seventh product to urea modification treatment;
[0118] The temperature of the first aluminum addition treatment is higher than the temperature of the second aluminum addition treatment.
[0119] In the present disclosure, "pH value of acid exchange treatment" refers to the pH value of the slurry obtained by contacting and mixing the NaY molecular sieve with the acidic solution, which is controlled by the amount of the acidic solution added.
[0120] In the present disclosure, the pH values are all tested values at room temperature (25° C.).
[0121] In the present disclosure, controlling the content of Na2O in the third product can make the prepared Y-type molecular sieve have a larger mesoporous specific surface area.
[0122] According to one embodiment of the present disclosure, the pH value of the acid exchange treatment is 2.8-3.1, and the above pH value range can improve the relative crystallinity of the Y-type molecular sieve.
[0123] According to one embodiment of the present disclosure, the silicon-aluminum ratio of the NaY molecular sieve is 4.8-5.0, the silicon-aluminum ratio is the molar ratio of SiO2 to Al2O3 in the NaY molecular sieve, and the crystallinity is above 80%.
[0124] According to one embodiment of the present disclosure, step a comprises: contacting the NaY molecular sieve with an acidic solution, performing an acid exchange treatment, and then performing solid-liquid separation, washing and drying treatment on the obtained mixture to obtain a first product. The acid exchange treatment in step a can promote the removal of skeleton aluminum in the subsequent preparation process of the Y-type molecular sieve, so that the prepared Y-type molecular sieve has a richer mesoporous structure; wherein the solid-liquid separation method is conventional in the art, for example, it can be centrifugal separation, filtration, etc.; the conditions for the drying treatment are conventional in the art and are not specifically required herein.
[0125] According to one embodiment of the present disclosure, the acidic solution is conventional in the art, for example, it may include one or more of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, citric acid solution, oxalic acid solution and tartaric acid solution. The present disclosure does not specifically limit the concentration of the acidic solution.
[0126] According to one embodiment of the present disclosure, the conditions for the acid exchange treatment include: a temperature of 30-80°C, preferably 35-70°C; and a time of 0.5-2h, preferably 0.5-1h.
[0127] In the present disclosure, the hydrothermal calcination process is well known to those skilled in the art.
[0128] According to one embodiment of the present disclosure, in order to improve the thermal stability of Y-type molecular sieve, in step b, the conditions for the first hydrothermal calcination treatment include: the treatment atmosphere is 100% water vapor atmosphere, the temperature is 500-600°C, preferably 550-600°C; the time is 1-3h, preferably 1-2h.
[0129] According to one embodiment of the present disclosure, in step c, the first ammonium exchange treatment includes: contacting the second product with an aqueous solution containing an ammonium salt to perform a first ammonium exchange treatment; the present disclosure does not specifically limit the concentration of the aqueous solution containing the ammonium salt, and the ammonium salt includes one or more of ammonium sulfate, ammonium chloride and ammonium nitrate; the weight ratio of the ammonium salt to the second product calculated on a dry basis is (0.1-1):1; the conditions for the first ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C.
[0130] According to one embodiment of the present disclosure, in order to improve the thermal stability of the Y-type molecular sieve, in step d, the conditions for the second hydrothermal roasting treatment include: the treatment atmosphere is 100% water vapor atmosphere, the temperature is 550-750°C, preferably 600-700°C, and more preferably 620-680°C; the time is 0.5-4h, preferably 1-2.5h.
[0131] According to one embodiment of the present disclosure, step e comprises: adding water to the fourth product for slurrying, contacting the obtained slurry with an alkali, and performing an alkali treatment to obtain a mixed slurry containing the fifth product. The present disclosure does not impose any specific restriction on the amount of water used, and the solid content of the slurry can be, for example, 10 weight %.
[0132] According to one embodiment of the present disclosure, in step e, the type of base is well known to those skilled in the art, for example, the base includes an inorganic base, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide and ammonia water.
[0133] According to one embodiment of the present disclosure, in step e, the weight ratio of the fourth product to the base on a dry basis is 1:(0.02-0.5), preferably 1:(0.05-0.4).
[0134] According to one embodiment of the present disclosure, in step e, the conditions for alkali treatment include: time of 0.5-6h and temperature of 25-100°C.
[0135] According to one embodiment of the present disclosure, in step f, the aluminum-containing compound includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum acetate and sodium aluminate.
[0136] According to one embodiment of the present disclosure, in step f, the weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on an Al2O3 basis is 1:(0.03-0.3), preferably 1:(0.035-0.28).
[0137] According to one embodiment of the present disclosure, the conditions for the first stage of aluminum addition treatment include: time 0.5-3h, preferably 0.8-2.8h; temperature 70-100°C, preferably 75-98°C; the conditions for the second stage of aluminum addition treatment include: time 0.5-2h, preferably 0.8-1.8h; temperature 30-60°C, preferably 32-58°C.
[0138] According to one embodiment of the present disclosure, in step g, the second ammonium exchange treatment includes: contacting the sixth product with an aqueous solution containing an ammonium salt to perform a second ammonium exchange treatment; the present disclosure does not specifically limit the concentration of the aqueous solution containing the ammonium salt, and the ammonium salt includes one or more of ammonium sulfate, ammonium chloride and ammonium nitrate; the weight ratio of the ammonium salt to the sixth product on a dry basis is (0.1-1):1; the conditions for the second ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C.
[0139] In the present disclosure, washing is conventional in the art, for example, water washing, specifically, 5-10 times the weight of water can be used to rinse the solid.
[0140] According to one embodiment of the present disclosure, step c also includes: subjecting the mixture obtained from the first ammonium exchange treatment to solid-liquid separation, washing and drying to obtain a third product; wherein the drying method is conventional in the art and no specific requirements are made herein; the solid-liquid separation method is conventional in the art, for example, it may be centrifugal separation, filtration, etc.
[0141] According to one embodiment of the present disclosure, step g also includes: solid-liquid separation, washing and drying the mixture obtained by the second ammonium exchange treatment to obtain a seventh product; wherein the drying method is conventional in the art and no specific requirements are made herein; the solid-liquid separation method is conventional in the art, for example, it can be centrifugal separation, filtration, etc.
[0142] According to one embodiment of the present disclosure, in step h, the urea modification treatment includes: contacting the seventh product with a urea solution, and drying the obtained solid product; the weight ratio of the seventh product to urea on a dry basis is 1:(0.02-0.3); the contact conditions include: time is 0.1-12h, temperature is 25-100°C; the drying conditions include: time is 0.5-10h, temperature is 50-105°C; the drying method can be drying in a drying oven.
[0143] According to one embodiment of the present disclosure, the pore size of the carrier is 3-20 nm, preferably 5-15 nm, and more preferably 6-12 nm.
[0144] According to one embodiment of the present disclosure, the pore concentration of the carrier is greater than 0.3, preferably greater than 0.5, more preferably greater than 1.0, and further preferably greater than 1.2.
[0145] According to one embodiment of the present disclosure, there is no specific limitation on the morphology of the carrier, for example, it can be in the shape of microspheres, spheres, tablets or strips, and the molding treatment method is also conventional in the art; step S1 comprises: mixing the mesoporous Y-type molecular sieve, the heat-resistant inorganic component source, the molding component and the optional acidic component source, and then extruding and calcining to obtain the carrier; the molding component comprises an extrusion aid and / or an adhesive; the calcining treatment conditions include: the time is 1-10h, preferably 2-8h; the temperature is 350-800°C, preferably 450-650°C.
[0146] In the present disclosure, the extrusion aid includes one or more of carboxylic acid, polyol, organic amine and surfactant; wherein the carboxylic acid includes one or more of monocarboxylic acid with carbon number of 1-10 and dicarboxylic acid with carbon number of 2-10, including but not limited to formic acid, acetic acid, oxalic acid, propionic acid, malonic acid, butyric acid, succinic acid, glutaric acid, adipic acid, benzoic acid, phthalic acid, phenylpropionic acid, etc.; the polyol includes one or more of saturated diol with carbon number of 2-5 and saturated triol with carbon number of 3-5, including but not limited to ethylene glycol, butanediol, propylene glycol, etc.; the organic amine includes one or more of urea and alcoholamine with carbon number of 1-5, and the carbon atom is 1-5. The alcohol amines with a molecular number of 1-5 include but are not limited to monoethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, etc.; the surfactants include anionic surfactants, cationic surfactants, zwitterionic surfactants, nonionic surfactants, etc., among which anionic surfactants include but are not limited to stearic acid, sodium dodecylbenzene sulfonate, etc., cationic surfactants include but are not limited to quaternary ammonium compounds, etc., zwitterionic surfactants include but are not limited to lecithin, amino acid type, betaine type, etc., nonionic surfactants include but are not limited to fatty acid sorbitan (Span), polysorbate (Tween), polyoxyethylene type, polyoxyethylene-polyoxypropylene copolymer, etc.
[0147] According to one embodiment of the present disclosure, the adhesive includes one or more of nitric acid, citric acid, cellulose derivatives, starch and starch derivatives; among which, the cellulose derivatives are such as carboxymethyl cellulose, hydroxypropyl cellulose, etc. The present disclosure does not limit the molecular weight of the above substances.
[0148] According to one embodiment of the present disclosure, the heat-resistant inorganic component source includes a heat-resistant inorganic oxide and / or a heat-resistant inorganic oxide precursor; the heat-resistant inorganic oxide precursor refers to a compound that can form a heat-resistant inorganic oxide after calcination, usually one or more of a salt, a hydroxide, a hydrated oxide, a gel of a hydroxide and a sol of a hydroxide; preferably, the heat-resistant inorganic oxide includes one or more of SiO2, Al2O3, MgO, ZrO2, TiO2 and CaO, and the heat-resistant inorganic oxide precursor includes one or more of silica sol, water glass, pseudo-boehmite, Mg(OH)2, MgCO3, hydrated titanium oxide, titanyl sulfate and Ca(OH)2, CaCO3.
[0149] In the present disclosure, the amounts of the Y-type molecular sieve, the heat-resistant inorganic component source, the molding component and the acidic component source are conventional in the art. For example, the weight ratio of the heat-resistant inorganic component, the mesoporous Y-type molecular sieve and the molding component, calculated as oxides, can be 100:(0.1-50):(0.5-10).
[0150] In the present disclosure, the acidic component source is a substance that is prepared to be able to serve as an acidic component in a carrier.
[0151] According to an embodiment of the present disclosure, step S2 includes:
[0152] A. contacting the carrier with a mixed solution containing an active metal source to obtain a pre-product;
[0153] B. Drying and calcining the pre-product.
[0154] The present disclosure has no particular limitation on the conditions of the contact reaction, and for example, the conditions may include: a time of 0.5-12 h and a temperature of 5-150° C.
[0155] According to one embodiment of the present disclosure, in step B, the conditions for the drying treatment include: time of 0.5-24h, preferably 1-12h; temperature of 80-350°C, preferably 100-300°C.
[0156] According to one embodiment of the present disclosure, in step B, the conditions for the calcination treatment include: time of 0.2-12h, preferably 1-10h; temperature of 360-700°C, preferably 400-650°C, and the calcination treatment method can be, for example, a muffle furnace, a mesh belt furnace, a converter, etc.
[0157] According to one embodiment of the present disclosure, the active metal source includes a soluble compound of a Group VIII metal and / or a soluble compound of a Group VIB metal; the types of soluble compounds of Group VIII metals are well known to those skilled in the art, and for example, can be selected from one or more of nitrates of Group VIII metals, soluble acetates of Group VIII metals, soluble carbonates of Group VIII metals, chlorides of Group VIII metals, and soluble complexes of Group VIII metals. Preferably, the soluble metal compound of Group VIII metals includes one or more of nickel nitrates, nickel acetates, soluble carbonates of nickel, chlorides of nickel, and soluble complexes of nickel; the types of soluble compounds of Group VIB metals are well known to those skilled in the art, and preferably, the soluble compound of Group VIB metals includes one or more of molybdic acid, paramolybdic acid, soluble molybdates, soluble paramolybdates, tungstic acid, metatungstic acid, ethyl metatungstic acid, soluble tungstates, and soluble metatungstates; further preferably The active metal source includes a soluble compound of a Group VIII metal and a soluble compound of a Group VIB metal, the soluble compound of a Group VIB metal includes one or more of molybdic acid, paramolybdic acid, soluble molybdates and soluble paramolybdates, and one or more of tungstic acid, metatungstic acid, ethyl metatungstic acid, soluble tungstates and soluble metatungstates; calculated as oxides, the total weight ratio of molybdenum element and tungsten element to the weight ratio of nickel element is 1:(0.01-10), and the present disclosure has no limitation on the weight ratio of molybdenum oxide and tungsten oxide.
[0158] According to one embodiment of the present disclosure, relative to the total weight of the carrier and the active metal source, the amount of the carrier is 40-99.9% by weight, preferably 50-90% by weight; the amount of the active metal source is 0.1-60% by weight, preferably 10-50% by weight, and the weight of the active metal source is calculated as oxide.
[0159] A second aspect of the present disclosure provides a method for preparing a hydrocracking catalyst using the method described in the first aspect of the present disclosure.
[0160] According to one embodiment of the present disclosure, the hydrocracking catalyst comprises a carrier and a metal active component supported on the carrier, wherein the carrier comprises a mesoporous Y-type molecular sieve;
[0161] The hydrocracking catalyst has a pore size of 3-20 nm and a pore size concentration of more than 0.3.
[0162] The hydrocracking catalyst disclosed in the present invention has a suitable geometric structure, and its use in the hydrocracking reaction of hydrocarbon feedstock oil is beneficial to the diffusion of reactants and products, and further beneficial to the conversion of cycloalkanes; and the catalyst has a high acid density, which can improve the catalytic activity and stability.
[0163] In the present disclosure, "pore size" refers to the pore size corresponding to the maximum value of dV / dr in the distribution curve of the differential of specific pore volume to pore size obtained when the pore structure of the sample is measured by the BET method. The pore size can be one or more, generally 1-3; according to one embodiment of the present disclosure, the pore size of the hydrocracking catalyst is 3-20nm, preferably 5-12nm.
[0164] In the present disclosure, "pore size concentration" refers to the dV / dr value corresponding to the most probable pore size in the distribution curve of the differential of specific pore volume versus pore size obtained when the pore structure of the sample is measured using the BET method; the larger the value, the higher the pore size concentration; according to one embodiment of the present disclosure, the pore size concentration of the hydrocracking catalyst is greater than 0.3, preferably greater than 0.5, more preferably greater than 1.0, and further preferably greater than 1.2.
[0165] According to one embodiment of the present disclosure, the metal active component includes a metal oxide, preferably an oxide of a Group VIII metal and / or an oxide of a Group VIB metal. The oxide of the Group VIII metal may, for example, include one or more of nickel oxide, cobalt oxide and iron oxide. The oxide of the Group VIB metal may, for example, include molybdenum oxide and / or tungsten oxide. Preferably, the metal active component includes nickel oxide, molybdenum oxide and tungsten oxide, and the weight ratio of the total weight of the molybdenum oxide calculated as the molybdenum element and the tungsten oxide calculated as the tungsten element to the nickel oxide calculated as the nickel element is 1:(0.01-10). The present disclosure has no limitation on the weight ratio of the molybdenum oxide and the tungsten oxide.
[0166] According to one embodiment of the present disclosure, the carrier also includes a heat-resistant inorganic component and an optional acidic component. The present disclosure does not impose any restrictions on the type of the acidic component, which may be a material with a characteristic crystalline structure or an amorphous phase material. The present disclosure does not impose any restrictions on the amount, composition, etc. of the acidic component; for example, it may include one or more of ZRP molecular sieve, mordenite, ZSM-5 molecular sieve, MCM-41 molecular sieve, Ω molecular sieve, ZSM-12 molecular sieve, MCM-22 molecular sieve and composite metal oxide; the above molecular sieves may be commercially available products or may be prepared using conventional techniques in the art; the composite metal The metal oxide includes more than two components; preferably, the composite metal oxide includes one or more of aluminum-silicon composite oxide, aluminum-titanium composite oxide, aluminum-magnesium composite oxide, silicon-magnesium composite oxide, silicon-zirconium composite oxide, silicon-thorium composite oxide, silicon-beryllium composite oxide, silicon-titanium composite oxide and titanium-zirconium composite oxide, and can be specifically silicon-aluminum composite oxide; the heat-resistant inorganic component is obtained by a heat-resistant inorganic component source through subsequent preparation steps, and the contents of the heat-resistant inorganic component and the acidic component are conventional in the art, and the present disclosure does not make specific requirements. For example, relative to the total weight of the carrier, the content of the acidic component can be 0.1-50 weight%.
[0167] According to one embodiment of the present disclosure, the content of the carrier is 40-99.9 wt%, preferably 50-90 wt%, relative to the total weight of the hydrocracking catalyst; the content of the metal active component is 0.1-60 wt%, preferably 10-50 wt%, calculated as oxide.
[0168] In the present disclosure, the carrier or catalyst may have various morphologies as required, such as microspheres, spheres, tablets or strips.
[0169] The third aspect of the present disclosure provides a method for a hydrocracking reaction, comprising: contacting a hydrocarbon feedstock oil, a catalyst and hydrogen, and performing the hydrocracking reaction, wherein the catalyst comprises the hydrocracking catalyst described in the second aspect of the present disclosure.
[0170] According to one embodiment of the present disclosure, the conditions for the hydrocracking reaction are conventional in the art, for example, including: a temperature of 200-650°C, preferably 300-510°C; a pressure of 3-24MPa, preferably 4-15MPa; a liquid hourly space velocity of 0.1-30h -1 The hydrogen-to-oil volume ratio is 600-1500, where the "hydrogen-to-oil volume ratio" refers to the volume ratio of hydrogen to hydrocarbon feedstock oil.
[0171] According to one embodiment of the present disclosure, the boiling point of the hydrocarbon feedstock oil is 370-690°C; preferably, the hydrocarbon feedstock oil includes one or more of vacuum gas oil, demetallized oil, atmospheric residue oil, deasphalted vacuum residue oil, vacuum residue oil, coking distillate oil, shale oil, asphalt sand oil and coal liquefaction oil.
[0172] According to one embodiment of the present disclosure, the method further comprises: in the presence of hydrogen, subjecting the hydrocracking catalyst and the sulfur-containing material to a presulfurization treatment at 140-370° C.; the method and conditions for the above-mentioned presulfurization treatment are conventional in the art, and can be carried out outside the reactor or in-situ sulfurization in the reactor; the sulfur-containing material is conventional in the art, for example, it can be hydrogen sulfide.
[0173] The present disclosure will be further illustrated by examples below, but the present disclosure is not limited thereby. The instruments and reagents used in the examples of the present disclosure are all commonly used instruments and reagents by those skilled in the art unless otherwise specified.
[0174] The NaY molecular sieves in the examples and comparative examples were produced by the Qilu Branch of Catalyst Co., Ltd., and the unit cell parameters were The silicon-aluminum ratio is 4.8-5.0 and the crystallinity is 84.1%.
[0175] The unit cell parameters were determined using the RIPP145-90 standard method, which is described in Petrochemical Analysis Methods (RIPP Test Methods), edited by Yang Cuiding, Science Press, published in 1990.
[0176] The content of Na2O was determined using the GB / T30905-2014 standard method.
[0177] The relative crystallinity was measured using the RIPP146-90 standard method, which is described in Petrochemical Analysis Methods (RIPP Test Methods), edited by Yang Cuiding, published by Science Press in 1990.
[0178] The relative crystallinity of the present disclosure is crystallinity of examples / crystallinity of standard samples.
[0179] The standard sample used was NaY molecular sieve produced by Qilu Catalysis Company, and its crystallinity was set to 100%.
[0180] The method for determining the molecular sieve pore structure is as follows:
[0181] The AS-3 and AS-6 static nitrogen adsorption instruments produced by Quantachrome Instruments were used for determination.
[0182] Instrument parameters: The sample was placed in the sample handling system and vacuumed to 1.33×10 -2Pa, keep the temperature and pressure for 4 hours to purify the sample. At the liquid nitrogen temperature of -196 ° C, the adsorption and desorption of nitrogen by the purified sample under different pressure ratios P / P0 were tested to obtain the N2 adsorption-desorption isotherm curve.
[0183] Then, the two-parameter BET formula was used to calculate the total specific surface area and mesopore specific surface area. The adsorption amount below the specific pressure P / P0=0.98 was taken as the total pore volume of the sample. The pore size distribution of the mesopore part was calculated using the BJH formula, and the integral method was used to calculate the total volume of micropores and the total volume of mesopores.
[0184] The testing method of pore diameter: mercury intrusion method, refer to the method described in "Analysis, Test and Characterization of Industrial Catalysts" (China Petrochemical Press, first edition in 1990, edited by Liu Xiyao et al., Chapter 2 Determination of Catalyst Pore Structure).
[0185] Test method for pore concentration: mercury intrusion method, refer to the method described in "Analysis, Test and Characterization of Industrial Catalysts" (China Petrochemical Press, first edition in 1990, edited by Liu Xiyao et al., Chapter 2 Catalyst Pore Structure Determination).
[0186] Calculation method of conversion rate: The distillation range distribution of the raw oil and the distillate oil is determined by the ASTM D2887 gas chromatography method. The conversion ratio of the fraction above 350°C in the product is used for calculation, as shown in the following formula.
[0187]
[0188] The test method for the paraffin content in the tail oil is conventional in the art.
[0189] Testing method of BMCI value: refer to Petroleum Refining Engineering, edited by Lin Shixiong, Petroleum Industry Press, 2000, Beijing, P74.
[0190] Testing method of viscosity index: refer to Petroleum Refining Engineering, edited by Lin Shixiong, Petroleum Industry Press, 2000, Beijing, P82.
[0191] In the following Examples and Comparative Examples, the dry basis was measured by calcining the samples at 600° C. for 4 h.
[0192] Example 1
[0193] The Y-type molecular sieve A is prepared by the following steps:
[0194] a. Mixing NaY molecular sieve and hydrochloric acid solution to make pulp, the pH value of the pulp is 3.0, acid exchange treatment is carried out at 45° C. for 0.5 h, and the obtained mixture is filtered, washed and dried to obtain a first product;
[0195] The content of Na2O in the first product is less than 5 wt% based on the dry weight of the first product;
[0196] b. subjecting the first product to a first hydrothermal calcination treatment in a 100% water vapor atmosphere to obtain a second product;
[0197] The conditions of the first hydrothermal calcination treatment include: time of 2 h, temperature of 600 °C;
[0198] c. 100 g of the second product on a dry basis was mixed with an ammonium chloride solution (the weight ratio of ammonium chloride to water was 1:10) and slurried to perform a first ammonium exchange treatment to obtain a third product;
[0199] The conditions for the first ammonium exchange included: time of 1 h, temperature of 70°C;
[0200] Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %;
[0201] The weight ratio of ammonium chloride to the second product on a dry basis is 1:1;
[0202] d. subjecting the third product to a second hydrothermal calcination in a 100% water vapor atmosphere to obtain a fourth product;
[0203] The conditions of the second hydrothermal calcination treatment include: time of 2.5 h, temperature of 620°C;
[0204] e. The fourth product is slurried with water to obtain a molecular sieve slurry with a solid content of 10 wt %; NaOH (purity 96 wt %) is mixed with the above molecular sieve slurry and subjected to alkali treatment to obtain a mixed slurry containing the fifth product;
[0205] The conditions of the alkali treatment include: time of 0.5 h, temperature of 50°C;
[0206] The weight ratio of the fourth product to sodium hydroxide on a dry basis is 1:0.17;
[0207] f. contacting Al2(SO4)3 with the mixed slurry, sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment, and then filtering and washing the mixture to obtain a sixth product;
[0208] The weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on alumina basis is 1:0.05;
[0209] The conditions of the first aluminum treatment included: time of 0.5 h and temperature of 75°C;
[0210] The conditions of the second aluminum treatment included: time of 1 h, temperature of 58°C;
[0211] g. mixing the sixth product obtained in step f with an ammonium sulfate solution, performing a second ammonium exchange treatment, and then filtering, washing and drying;
[0212] The weight ratio of solid product, ammonium sulfate and water on a dry basis is 1:1:10;
[0213] The conditions of the second ammonium exchange treatment include: time of 1 h, temperature of 70°C;
[0214] h. The seventh product obtained in step g and urea are contacted with water, and the obtained solid is dried in a drying oven to obtain a Y-type molecular sieve A, the parameters of which are listed in Table 1;
[0215] The conditions of the contact treatment included: time of 0.5 h, temperature of 35°C;
[0216] The conditions of the drying treatment include: time of 6 h and temperature of 75°C;
[0217] The weight ratio of urea to the seventh product on a dry basis is 0.03:1.
[0218] Pore size distribution Figure 1 As shown, in Figure 1 In the figure, A represents mesopores with a pore size in the range of 3.0-4.5 nm, B represents mesopores with a pore size in the range of 5.5-11.0 nm, and C represents mesopores with a pore size in the range of 12.5-36.0 nm.
[0219] Example 2
[0220] The Y-type molecular sieve B is prepared by the following steps:
[0221] a. Mixing NaY molecular sieve and nitric acid solution to make pulp, wherein the pH value of the pulp is 2.8, and subjecting the mixture to acid exchange treatment at 70° C. for 1 h. Filtering, washing and drying the obtained mixture to obtain a first product;
[0222] The content of Na2O in the first product is less than 5 wt% based on the dry weight of the first product;
[0223] b. subjecting the first product to a first hydrothermal calcination treatment in a 100% water vapor atmosphere to obtain a second product;
[0224] The conditions of the first hydrothermal calcination treatment include: time of 2 h, temperature of 600 °C;
[0225] c. 100 g of the second product on a dry basis was mixed with an ammonium chloride solution (the weight ratio of ammonium chloride to water was 1:10) and slurried to perform a first ammonium exchange treatment to obtain a third product;
[0226] The conditions for the first ammonium exchange included: time of 1 h, temperature of 70°C;
[0227] Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %;
[0228] The weight ratio of ammonium chloride to the second product on a dry basis is 1:1;
[0229] d. subjecting the third product to a second hydrothermal calcination in a 100% water vapor atmosphere to obtain a fourth product;
[0230] The conditions of the second hydrothermal calcination treatment include: time of 1 h, temperature of 650°C;
[0231] e. The fourth product is slurried with water to obtain a molecular sieve slurry with a solid content of 10 wt %; NaOH (purity 96 wt %) is mixed with the above molecular sieve slurry and subjected to alkali treatment to obtain a mixed slurry containing the fifth product;
[0232] The conditions of the alkali treatment include: time of 0.5 h, temperature of 50°C;
[0233] The weight ratio of the fourth product to sodium hydroxide is 1:0.5 on a dry basis;
[0234] f. contacting AlCl3 with the mixed slurry, sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment, and then filtering and washing the mixture to obtain a solid product;
[0235] The weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on alumina basis is 1:0.29;
[0236] The conditions of the first aluminum treatment include: time of 3 h, temperature of 100 °C;
[0237] The conditions of the second aluminum treatment include: time of 0.5 h, temperature of 30°C;
[0238] g. mixing the sixth product obtained in step f with an ammonium chloride solution, performing a second ammonium exchange treatment, and then filtering, washing and drying;
[0239] The weight ratio of solid product, ammonium chloride and water on a dry basis is 1:1:10;
[0240] The conditions of the second ammonium exchange treatment included: time of 1 h, temperature of 70°C;
[0241] h. contacting the seventh product obtained in step g with urea and water, and drying the obtained solid in a drying oven to obtain a Y-type molecular sieve B, the parameters of which are listed in Table 1;
[0242] The conditions of the contact treatment included: time of 1 h, temperature of 40°C;
[0243] The conditions of drying treatment include: time 10 h, temperature 55°C;
[0244] The weight ratio of urea to the seventh product on a dry basis is 0.1:1;
[0245] Example 3
[0246] The Y-type molecular sieve C is prepared by the following steps:
[0247] a. Mixing NaY molecular sieve and sulfuric acid solution to make pulp, the pH value of the pulp is 2.6, acid exchange treatment is carried out at 60° C. for 1.5 h, and the obtained mixture is filtered, washed and dried to obtain a first product;
[0248] The content of Na2O in the first product is less than 5 wt% based on the dry weight of the first product;
[0249] b. subjecting the first product to a first hydrothermal calcination treatment in a 100% water vapor atmosphere to obtain a second product;
[0250] The conditions of the first hydrothermal calcination treatment include: time of 2 h, temperature of 600 °C;
[0251] c. 100 g of the second product on a dry basis was mixed with an ammonium chloride solution (the weight ratio of ammonium chloride to water was 1:10) and slurried to perform a first ammonium exchange treatment to obtain a third product;
[0252] The conditions for the first ammonium exchange included: time of 1 h, temperature of 70°C;
[0253] Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %;
[0254] The weight ratio of ammonium chloride to the second product on a dry basis is 1:1;
[0255] d. subjecting the third product to a second hydrothermal calcination in a 100% water vapor atmosphere to obtain a fourth product;
[0256] The conditions of the second hydrothermal calcination treatment include: time of 1 h, temperature of 680°C;
[0257] e. The fourth product is slurried with water to obtain a molecular sieve slurry with a solid content of 10 wt %; NaOH (purity 96 wt %) is mixed with the above molecular sieve slurry and subjected to alkali treatment to obtain a mixed slurry containing the fifth product;
[0258] The conditions of the alkali treatment include: time of 0.5 h, temperature of 50°C;
[0259] The weight ratio of the fourth product to sodium hydroxide on a dry basis is 1:0.4;
[0260] f. contacting Al(NO3)3·9H2O with the mixed slurry, sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment, and then filtering and washing the mixture to obtain a solid product;
[0261] The weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on alumina basis is 1:0.14;
[0262] The conditions of the first aluminum treatment include: time of 1 h, temperature of 90°C;
[0263] The conditions of the second aluminum treatment include: time of 0.5 h, temperature of 50°C;
[0264] g. mixing the sixth product obtained in step f with an ammonium chloride solution, performing a second ammonium exchange treatment, and then filtering, washing and drying;
[0265] The weight ratio of solid product, ammonium chloride and water on a dry basis is 1:1:10;
[0266] The conditions of the second ammonium exchange treatment included: time of 1 h, temperature of 70°C;
[0267] h. The seventh product obtained in step g and urea are contacted with water, and the obtained solid is dried in a drying oven to obtain a Y-type molecular sieve C, whose parameters are listed in Table 1;
[0268] The conditions of the contact treatment included: time of 2 h, temperature of 25°C;
[0269] The conditions of the drying treatment include: time of 8 h and temperature of 100°C;
[0270] The weight ratio of urea to the seventh product on a dry basis is 0.25:1.
[0271] Comparative Example 1
[0272] The Y-type molecular sieve DB1 was prepared by the following steps:
[0273] a. Mixing NaY molecular sieve and ammonium chloride solution (the weight ratio of ammonium chloride to water is 1:10) and performing a first ammonium exchange treatment. Filtering, washing and drying the obtained mixture to obtain product a;
[0274] The conditions of the first ammonium exchange treatment included: time of 0.5 h and temperature of 45°C;
[0275] The weight ratio of ammonium chloride to NaY molecular sieve on a dry basis is 1:1;
[0276] Based on the dry weight of product a, the content of Na2O in product a is less than 5 weight %;
[0277] b. subjecting product a to a first hydrothermal calcination in a 100% water vapor atmosphere to obtain product b;
[0278] The conditions of the first hydrothermal calcination treatment include: time of 1 h, temperature of 680°C;
[0279] c. Mixing product b with ammonium chloride solution and performing a second ammonium exchange treatment, filtering, washing and drying the obtained mixture to obtain product c;
[0280] The conditions of the second ammonium exchange treatment included: time of 1 h, temperature of 70°C;
[0281] The weight ratio of product b, ammonium chloride and water on a dry basis is 1:1:10;
[0282] Based on the dry weight of the product b, the content of Na2O in the product b is less than 3 weight %;
[0283] d. subjecting product c to a second hydrothermal calcination in a 100% water vapor atmosphere to obtain product d;
[0284] The conditions of the second hydrothermal calcination treatment include: time of 2.5 h, temperature of 620°C;
[0285] e. 100 g of the product d on a dry basis was slurried with water to obtain a molecular sieve slurry with a solid content of 10 wt %; NaOH (purity 96 wt %) was mixed with the molecular sieve slurry, and the mixture was treated with alkali at 50° C. for 0.5 h, and the obtained mixture was filtered, washed and dried to obtain a product e;
[0286] f. Mix the product e with an ammonium chloride solution and perform a third ammonium exchange treatment. Filter, wash and dry the obtained mixture to obtain a Y-type molecular sieve DB1, the parameters of which are listed in Table 1;
[0287] The conditions of the third ammonium exchange treatment include: time of 1 hour, temperature of 70°C;
[0288] The weight ratio of product e, ammonium chloride and water on a dry basis is 1:1:10.
[0289] Comparative Example 2
[0290] The Y-type molecular sieve DB2 was prepared by the following steps:
[0291] a. Mixing NaY molecular sieve and hydrochloric acid solution to make pulp, the pH value of the pulp is 4.0, acid exchange treatment is carried out at 45° C. for 0.5 h, and the obtained mixture is filtered, washed and dried to obtain product a;
[0292] Based on the dry weight of product a, the content of Na2O in product a is less than 5 weight %;
[0293] b. Performing a first hydrothermal calcination treatment in a 100% water vapor atmosphere to obtain product b;
[0294] The conditions of the first hydrothermal calcination treatment include: time of 2 h, temperature of 600 °C;
[0295] c. Mix 100 g of the product b on a dry basis with an ammonium chloride solution (the weight ratio of ammonium chloride to water is 1:10) and perform a first ammonium exchange treatment. Filter, wash and dry the mixture to obtain a product c.
[0296] The conditions for the first ammonium exchange included: time of 1 h, temperature of 70°C;
[0297] Based on the dry weight of the product c, the content of Na2O in the product c is less than 3 weight %;
[0298] The weight ratio of ammonium chloride to product c on a dry basis is 1:1;
[0299] d. subjecting product c to a second hydrothermal calcination treatment in a 100% water vapor atmosphere to obtain product d;
[0300] The conditions of the second hydrothermal calcination treatment include: time of 1 h, temperature of 680°C;
[0301] e. 100 g of product d was slurried with water to obtain a molecular sieve slurry with a solid content of 10 wt %; NaOH (purity 96 wt %) was mixed with the above molecular sieve slurry and subjected to alkali treatment to obtain a mixed slurry containing product e;
[0302] The conditions of the alkali treatment include: time of 0.5 h, temperature of 50°C;
[0303] The weight ratio of product d to sodium hydroxide on a dry basis is 1:0.11;
[0304] f. contacting Al2(SO4)3 with the mixed slurry to perform aluminum addition treatment, and then filtering and washing the mixture to obtain a solid product;
[0305] The weight ratio of product e calculated on a dry basis to the aluminum-containing compound calculated on alumina basis is 1:0.05;
[0306] The conditions for aluminum addition treatment include: time 0.5 h, temperature 70°C;
[0307] g. The solid product obtained in step f is mixed with an ammonium chloride solution and slurried, and subjected to a second ammonium exchange treatment, followed by washing, filtering and drying to obtain a Y-type molecular sieve DB2, the parameters of which are listed in Table 1;
[0308] The weight ratio of solid product, ammonium chloride and water on a dry basis is 1:1:10;
[0309] The conditions of the second ammonium exchange treatment include: time of 1 hour and temperature of 70°C.
[0310] Comparative Example 3
[0311] The Y-type molecular sieve DB3 was prepared by the method of Example 1, except that in step a, the pH value of the slurry was 3.6. The parameters of the prepared Y-type molecular sieve DB3 are listed in Table 1.
[0312] Comparative Example 4
[0313] The Y-type molecular sieve DB4 was prepared by the method of Example 1, except that in step a, the pH value of the slurry was 2.2. The parameters of the prepared Y-type molecular sieve DB4 are listed in Table 1.
[0314] Comparative Example 5
[0315] The Y-type molecular sieve DB5 was prepared by the method of Example 1, except that:
[0316] Step f: contacting Al2(SO4)3 with the mixed slurry to perform aluminum addition treatment, and then filtering and washing the mixture to obtain a solid product;
[0317] The conditions for the aluminum addition treatment include: time of 1 hour and temperature of 75° C.; the parameters of the prepared Y-type molecular sieve DB5 are listed in Table 1.
[0318] Comparative Example 6
[0319] Y-type molecular sieve DB6 was prepared by the method of Example 1, except that in step b, the content of Na2O in the third product was 4.0 wt% based on the dry weight of the third product; the parameters of the prepared Y-type molecular sieve DB6 are listed in Table 1.
[0320] Table 1
[0321]
[0322]
[0323] according to Figure 1From the results, it can be seen that the Y-type molecular sieve A prepared in Example 1 has mesopores with pore sizes in the range of 3-4.5nm, 5.5-11.0nm and 12.5-36nm; the molecular sieves of Examples 2 and 3 were subjected to pore distribution tests, which had mesopores with pore sizes in the range of 3-4.5nm, 5.5-11.0nm and 12.5-36nm.
[0324] Example 4
[0325] Take 40.3g of pseudo-boehmite CL-A (obtained from the catalyst Changling branch, dry basis 64.5%), 86.6g of siral40 (obtained from the catalyst Changling branch, produced by SASOL, with a silicon oxide content of 40.3%, dry basis 79.7%), 6.2g of Y-type molecular sieve A, and 3g of sesbania powder, mix them evenly for later use. Add water to 122mL of 1.4mL of concentrated nitric acid and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead for 3 times, and then use The extruded strips were dried at 120°C for 6 hours, and the dried strips were put into a roasting furnace and treated at 580°C for 3 hours, with an air flow rate of 40 L / h. The strips were cooled to room temperature and taken out, which was recorded as carrier A-1.
[0326] Based on 100g of the carrier, a mixed aqueous solution of nickel nitrate and ammonium metatungstate (both from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst of 23.0% by weight and the content of nickel oxide of 5.5% by weight, and the amount of water was adjusted. The porous carrier prepared by the pore saturation method was impregnated for 2 hours at a temperature of 30°C. The porous carrier obtained by impregnation was dried at 135°C for 6 hours, and then roasted at 420°C for 3 hours. During the roasting process, the air flow rate was maintained at not less than 37.5 cubic meters / (kg carrier·hour), thereby obtaining a hydrocracking catalyst AS.
[0327] Embodiment 5-6
[0328] The hydrocracking catalysts BS and CS were prepared by the method of Example 4, except that the Y-type molecular sieve A was replaced by Y-type molecular sieves B and C, respectively.
[0329] Comparative Examples 8-15
[0330] The hydrocracking catalyst was prepared by the method of Example 4, except that the Y-type molecular sieve A was replaced by the Y-type molecular sieve USY-A (obtained from Catalyst Changling Co., Ltd., unit cell constant Crystallinity 67.3%, mesoporous specific surface area 64m 2 / g) and Y-type molecular sieves prepared in Comparative Examples 1-6.
[0331] Catalyst evaluation
[0332] The catalysts prepared in the examples and comparative examples were used for the hydrocracking reaction of hydrocarbon feedstock oil. The catalyst evaluation adopted a one-pass process, a hydrocarbon sand light reduction two-line, and the properties of the feedstock oil are shown in Table 2.
[0333] Table 2
[0334] type Sand light minus two <![CDATA[Density (20 °C) / g / cm 3 > 0.9068 Refractive index (20℃) 1.4857 IBP - 5% 301℃ 50% 361℃ 95% 439℃
[0335] The catalyst was pre-sulfurized and then heated to 8.0 MPa with a volume space velocity of 0.85 h -1 , liquid hourly space velocity is 1.5h -1 The performance of the catalyst was investigated at 360°C, 370°C and 380°C with a hydrogen-to-oil ratio of 1200 v / v. The results are listed in Table 3.
[0336] In Table 3, "activity" refers to the reaction temperature required to achieve a conversion of 60% at >350°C.
[0337] Table 3
[0338]
[0339] According to the data in Table 3, the hydrocracking catalyst disclosed in the present invention is used for the hydrocracking reaction of hydrocarbon feedstock oil to obtain a higher tail oil paraffin content, a higher viscosity index and a lower tail oil BMCI value.
[0340] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0341] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0342] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a hydrocracking catalyst, characterized in that: The method comprises the following steps: S1, forming a Y-type molecular sieve rich in mesopores to obtain a carrier; S2, loading metal active components on the carrier; The unit cell parameter of the mesoporous Y-type molecular sieve is 24.35-24.55 angstroms, the relative crystallinity is more than 55%, and the specific surface area of the mesopores is 250-400 m 2 / g; The mesopore-rich Y-type molecular sieve has mesopores with pore diameters in the ranges of 3-4.5 nm, 5.5-11.0 nm and 12.5-36 nm.
2. The method according to claim 1, wherein: The unit cell parameters of the Y-type molecular sieve are 24.40-24.52 angstroms, and the specific surface area of the mesopores is 270-350 m 2 / g, and the relative crystallinity is 56-70%.
3. The method according to claim 1, wherein: The total volume of mesopores with pore sizes in the range of 3–4.5 nm is 0.038–0.045 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 5.5 to 11.0 nm is 0.015 to 0.020 cm 3 / g, and the total volume of mesopores with pore diameters ranging from 12.5 to 36 nm is 0.350 to 0.410 cm 3 / g; The total volume of the micropores is 0.180-0.300 cm 3 / g, and the total volume of the mesopores is 0.403-0.475cm 3 / g, with a total pore volume of 0.583-0.775 cm 3 / g, total specific surface area is 700-800m 2 / g; The total volume of mesopores accounts for 53-70% of the total pore volume.
4. The method according to claim 1, wherein: The method for preparing the mesoporous Y-type molecular sieve comprises the following steps: a. subjecting the NaY molecular sieve to an acid exchange treatment to obtain a first product, wherein the pH value of the acid exchange treatment is 2.5-3.5; b. subjecting the first product to a first hydrothermal roasting treatment to obtain a second product; c. subjecting the second product to a first ammonium exchange treatment to obtain a third product; Based on the dry weight of the third product, the content of Na2O in the third product is less than 3 weight %; d. subjecting the third product to a second hydrothermal roasting treatment to obtain a fourth product; e. contacting the fourth product, alkali and water, and performing alkali treatment to obtain a mixed slurry containing a fifth product; f. contacting the aluminum-containing compound with the mixed slurry, and sequentially performing a first stage aluminum addition treatment and a second stage aluminum addition treatment; g. subjecting the sixth product obtained in step f to a second ammonium exchange treatment to obtain a seventh product; h. subjecting the seventh product to urea modification treatment; The temperature of the first aluminum addition treatment is higher than the temperature of the second aluminum addition treatment.
5. The method according to claim 4, wherein: Step a comprises: contacting the NaY molecular sieve with an acidic solution, performing the acid exchange treatment, and then performing solid-liquid separation, washing and drying treatment on the obtained mixture to obtain the first product; The acidic solution includes one or more of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, citric acid solution, oxalic acid solution and tartaric acid solution; The conditions of the acid exchange treatment include: temperature of 30-80°C, preferably 35-70°C; time of 0.5-2h, preferably 0.5-1h; The silicon-aluminum ratio of the NaY molecular sieve is 4.8-5.0, and the crystallinity is above 80%. The silicon-aluminum ratio is the molar ratio of SiO2 to Al2O3 in the NaY molecular sieve; The pH value of the acid exchange treatment is 2.8-3.
1.
6. The method according to claim 4, wherein: In step b, the conditions of the first hydrothermal calcination treatment include: the treatment atmosphere is 100% water vapor atmosphere, the temperature is 500-600° C., and the time is 1-3 hours.
7. The method according to claim 4, wherein: The first ammonium exchange treatment comprises: contacting the second product with an aqueous solution containing an ammonium salt to perform the first ammonium exchange treatment; The weight ratio of the ammonium salt to the second product on a dry basis is 1:(0.1-1); The conditions of the first ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C; The second ammonium exchange treatment comprises: contacting the sixth product with an aqueous solution containing an ammonium salt to perform the second ammonium exchange treatment; The weight ratio of the ammonium salt to the sixth product on a dry basis is 1:(0.1-1); The conditions of the second ammonium exchange treatment include: time of 0.5-8h, temperature of 25-100°C; The ammonium salt includes one or more of ammonium chloride, ammonium sulfate and ammonium nitrate.
8. The method according to claim 4, wherein: In step d, the conditions of the second hydrothermal roasting treatment include: the treatment atmosphere is 100% water vapor atmosphere, the temperature is 550-750° C., preferably 600-700° C.; the time is 0.5-4 h, preferably 1-2.5 h.
9. The method according to claim 4, wherein: In step e, the base includes an inorganic base, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide and ammonia water; The weight ratio of the fourth product to the base on a dry basis is 1:(0.02-0.5), preferably 1:(0.05-0.4); The conditions of the alkali treatment include: time of 0.5-6h and temperature of 25-100°C.
10. The method according to claim 4, wherein: In step f, the aluminum-containing compound includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum acetate and sodium aluminate; The weight ratio of the fifth product calculated on a dry basis to the aluminum-containing compound calculated on an Al2O3 basis is 1:(0.03-0.3), preferably 1:(0.035-0.28); The conditions of the first stage of aluminum addition treatment include: time of 0.5-3h, temperature of 70-100°C; The conditions of the second stage of aluminum addition treatment include: time of 0.5-2h, temperature of 30-60°C.
11. The method according to claim 4, wherein: In step h, the urea modification treatment includes: contacting the seventh product, urea and water, and drying the obtained solid product; The weight ratio of the seventh product to the urea on a dry basis is 1:(0.02-0.3); The contact conditions include: time of 0.1-12h, temperature of 25-100°C; The drying conditions include: time of 0.5-10 hours and temperature of 50-105°C.
12. The method according to claim 1, wherein: The carrier has a pore size of 3-20 nm and a pore size concentration of more than 0.
3.
13. The method according to claim 1, wherein: Step S1 comprises: mixing the mesoporous Y-type molecular sieve, a heat-resistant inorganic component source, a molding component and an optional acidic component source, and then extruding and molding and calcining to obtain the carrier; The heat-resistant inorganic component source includes a heat-resistant inorganic oxide and / or a heat-resistant inorganic oxide precursor; Preferably, the heat-resistant inorganic oxide includes one or more of SiO2, Al2O3, MgO, ZrO2, TiO2 and CaO; The heat-resistant inorganic oxide precursor includes one or more of silica sol, water glass, pseudo-boehmite, Mg(OH)2, MgCO3, hydrated titanium oxide, titanyl sulfate, Ca(OH)2 and CaCO3; The molding components include an extrusion aid and / or an adhesive; Preferably, the extrusion aid includes one or more of a monocarboxylic acid having 1 to 10 carbon atoms, a dicarboxylic acid having 2 to 10 carbon atoms, a saturated diol having 2 to 5 carbon atoms, a saturated triol having 3 to 5 carbon atoms, urea, an alcoholamine having 1 to 5 carbon atoms, and a surfactant; The adhesive comprises one or more of nitric acid, citric acid, cellulose derivatives, starch and starch derivatives; The calcination conditions include: a calcination time of 1-10 hours and a temperature of 350-800°C.
14. The method according to claim 1, wherein: Step S2 includes: A. contacting the carrier with a mixed solution containing an active metal source to obtain a pre-product; B. drying and calcining the pre-product; The active metal source includes a soluble compound of a Group VIII metal and / or a soluble compound of a Group VIB metal; In step A, the contact reaction conditions include: time of 0.5-12h, temperature of 5-150°C; In step B, the drying conditions include: time of 0.5-24h, temperature of 80-350°C; The conditions of the calcination treatment include: time of 0.2-12h, temperature of 360-700°C; Optionally, relative to the total weight of the carrier and the active metal source, the amount of the carrier is 40-99.9 wt %, the amount of the active metal source is 0.1-60 wt %, and the weight of the active metal source is calculated as oxide.
15. A hydrocracking catalyst prepared by the method according to any one of claims 1 to 14.
16. The hydrocracking catalyst according to claim 15, wherein The hydrocracking catalyst comprises a carrier and a metal active component supported on the carrier, wherein the carrier comprises the mesoporous Y-type molecular sieve; Optionally, the hydrocracking catalyst has a pore size of 3-20 nm and a pore size concentration of 0.3 or more.
17. The hydrocracking catalyst according to claim 16, wherein The metal active component comprises a metal oxide, preferably an oxide of a Group VIII metal and / or an oxide of a Group VIB metal; The carrier also includes a heat-resistant inorganic component and an optional acidic component; The acidic component includes one or more of ZRP molecular sieve, mordenite, ZSM-5 molecular sieve, MCM-41 molecular sieve, Ω molecular sieve, ZSM-12 molecular sieve, MCM-22 molecular sieve and composite metal oxide; Preferably, the composite metal oxide includes one or more of aluminum silicon composite oxide, aluminum titanium composite oxide, aluminum magnesium composite oxide, silicon magnesium composite oxide, silicon zirconium composite oxide, silicon thorium composite oxide, silicon beryllium composite oxide, silicon titanium composite oxide and titanium zirconium composite oxide.
18. The hydrocracking catalyst according to claim 16, wherein Relative to the total weight of the hydrocracking catalyst, the content of the carrier is 40-99.9% by weight, and the content of the metal active component is 0.1-60% by weight, calculated as oxide.
19. A method for a hydrocracking reaction, the method comprising: The hydrocarbon feedstock oil, the catalyst and hydrogen are contacted to carry out the hydrocracking reaction, wherein the catalyst comprises the hydrocracking catalyst according to any one of claims 16 to 18.
20. The method according to claim 19, wherein: The conditions of the hydrocracking reaction include: temperature of 200-650°C, pressure of 3-24 MPa, liquid hourly space velocity of 0.1-30 h -1 , the volume ratio of hydrogen to oil is 600-1500.
21. The method according to claim 19, wherein: The boiling point of the hydrocarbon feedstock oil is 370-690°C; Preferably, the hydrocarbon feedstock oil includes one or more of vacuum gas oil, demetallized oil, atmospheric residue oil, deasphalted vacuum residue oil, vacuum residue oil, coking distillate oil, shale oil, asphalt sand oil and coal liquefaction oil.
Citation Information
Patent Citations
Y-type molecular sieve with ultra-high mesoporous content and preparation method of Y-type molecular sieve
CN104760973A
Preparation method for hydrocracking catalyst carrier
CN104826667A
Preparation method of small-grain Y-type molecular sieve
CN104828838B
A hierarchical porous FAU structure molecular sieve and its preparation method
CN110937609B
Preparation method of Y-type zeolite molecular sieve with mesoporous-micro hierarchical pore structure
CN111689504A